Antioxidant, Cytotoxic, and Antimicrobial Potential of Silver Nanoparticles Synthesized using Tradescantia pallida Extract - Shahzadi, Irum; Aziz Shah, Syed Munawar; Shah, Mohammad Maroof; Ismail, Tariq; Fatima, Nighat; Siddique, Maria; Waheed, Ummara; Baig, Ayesha; Ayaz, Aisha (Frontiers in Bioengineering and Biotechnology, 2022)
Silver nanoparticles have received much attention, due to their wide range of biological applications as an alternative therapy for disease conditions utilizing the nanobiotechnology domain for synthesis. The current study was performed to examine the antioxidant, anticancer, antibacterial and antifungal potential of biosynthesized silver nanoparticles using plant extract. The silver nanoparticles (TpAgNPs) were produced by reacting the T. pallida extract of and AgNO3 solution in nine various concentrations ratios subjected to bioactivities profiling. According to the current findings plant extract comprising of phenolics, flavonoids, and especially anthocyanins played a critical role in the production of TpAgNPs. UV-visible spectroscopy also validated the TpAgNPs formation in the peak range of 401-441 nm with medium concentration. FTIR analysis revealed that the Ag ion was stabilized by phytochemicals of T. pallida. The crystalline structure of TpAgNPs with the pattern of four diffraction peaks was verified with XRD and SEM images further validated the spherical shape of TpAgNPs. Among all TpAgNPs, the biosynthesized TpAgNP6 with a medium concentration ratio (5:10) and plant extract had the effective antioxidant potential of 77.2 ± 1.0% and 45.1± 0.5% free radical scavenging activity respectively. The cytotoxic activity of TpAgNP6 in comparison to plant extract for rhabdomyosarcoma cell line was significantly lowest with IC50 value of 81.5 ± 1.9 and 90.59 ± 1.6 µg/ml respectively and cell viability % of 24.3 ± 1.62 and 27.4 ± 1.05 respectively. The antibacterial and antifungal results of TpAgNPs revealed significant improvement in comparison to plant extract i.e minimum inhibitory concentration (MIC) 64 µg/ml against gram-negative P. aeruginosa while in the case of antifungal assay TpAgNP6 were active against C. parapsilosis. These TpAgNPs play a crucial role in determining the therapeutic potential of T. palida due to their biological efficacy.